Pengaruh Perbedaan Metode Pembentukan Terhadap Kelarutan Naringenin dalam Kokristal Naringenin-Asam Maleat - Andini Maulinariska (Fakultas Farmasi, 2026)
Naringenin is a flavonoid compound with various pharmacological activities; however, its pharmaceutical application is limited by low aqueous solubility, resulting in poor oral bioavailability. According to the Biopharmaceutical Classification System (BCS), naringenin is classified as a class II compound, characterized by low solubility and high permeability. Therefore, an effective approach is required to enhance its solubility without modifying its chemical structure. One promising strategy is cocrystal formation, which involves the combination of an active pharmaceutical ingredient and a neutral coformer in a specific stoichiometric ratio through non-covalent interactions, leading to modification of crystal lattice energy and improved solubility. In this study, maleic acid was selected as a coformer due to its functional groups capable of forming hydrogen bonds with naringenin. The selection was supported by computational analysis based on synthon prediction and energy minimization, which indicated favorable interaction stability between naringenin and maleic acid. Naringenin maleic acid cocrystals in a 1:1 molar ratio were prepared using solvent evaporation and slurry methods with ethanol as the solvent. The resulting cocrystals were characterized using PXRD (Powder X-Ray Diffractometer), DSC (Differential Scanning Calorimeter), FTIR (Fourier Transform Infrared Spectrophotometer), and SEM (Scanning Electron Microscope) to confirm the formation of a new crystalline phase and to evaluate differences in crystal structure and morphology. Solubility studies were conducted in aqueous media and quantified using UV–Vis spectrophotometry, followed by statistical analysis. The characterization results confirmed the formation of a new crystalline phase for both preparation methods. The aqueous solubility of naringenin increased significantly from 1.741 mg/L for the pure compound to 16.653 mg/L and 6.169 mg/L for cocrystals prepared by solvent evaporation and slurry methods, corresponding to 9.769-fold and 3.543-fold increases, respectively.
Reuploud Repository hasyim Juni 2026 Finalisasi Repo 23 Juni 2026_Yudi
Keywords: naringenin; maleic acid; solubility enhancement; preparation method